Relationship of aerobic fitness and motor skills with memory and attention in preschoolers (Ballabeina): A cross-sectional and longitudinal study - Barral Jérôme; Schindler Christian; Hartmann Tim; Gut Janine; Kriemler Susi; Niederer Iris; Puder Jardena J (BMC, 2011)
Abstract Background The debate about a possible relationship between aerobic fitness and motor skills with cognitive development in children has recently re-emerged, because of the decrease in children's aerobic fitness and the concomitant pressure of schools to enhance cognitive performance. As the literature in young children is scarce, we examined the cross-sectional and longitudinal relationship of aerobic fitness and motor skills with spatial working memory and attention in preschool children. Methods Data from 245 ethnically diverse preschool children (mean age: 5.2 (0.6) years, girls: 49.4%) analyzed at baseline and 9 months later. Assessments included aerobic fitness (20 m shuttle run) and motor skills with agility (obstacle course) and dynamic balance (balance beam). Cognitive parameters included spatial working memory (IDS) and attention (KHV-VK). All analyses were adjusted for age, sex, BMI, migration status, parental education, native language and linguistic region. Longitudinal analyses were additionally adjusted for the respective baseline value. Results In the cross-sectional analysis, aerobic fitness was associated with better attention (r = 0.16, p = 0.03). A shorter time in the agility test was independently associated with a better performance both in working memory (r = -0.17, p = 0.01) and in attention (r = -0.20, p = 0.01). In the longitudinal analyses, baseline aerobic fitness was independently related to improvements in attention (r = 0.16, p = 0.03), while baseline dynamic balance was associated with improvements in working memory (r = 0.15, p = 0.04). Conclusions In young children, higher baseline aerobic fitness and motor skills were related to a better spatial working memory and/or attention at baseline, and to some extent also to their future improvements over the following 9 months. Trial Registration clinicaltrials.gov NCT00674544